Amidase Activity of Urokinase I. Hydrolysis of a-N-Acetyl-L-Lysine p-Nitroanilide - Petkov, D; Christova, E; Karadjova, M (Thrombosis and Haemostasis, 1973)
α-N-acetyl-L-lysine p-nitroanilide (ALNA) was synthesized as a low-molecular weight model of the natural urokinase substrate plasminogen. Urokinase was found to catalyse anilide bond cleavage. The extent of hydrolysis can be followed spectro- photometrically by using the strong absorption band of one of the products p-nitro- aniline. An accurate, continuous and convenient assay for urokinase is proposed. As determined by the kinetic study, Vmax5 a measure for the sensitivity of an assay, is about 8 times higher than that obtained for the most sensitive urokinase ester substrates. This was demonstrated by its use for tracing the elution of urokinase during the purification of the enzyme by column chromatography.The high apparant Km value obtained is discussed in terms of the mechanism of serine proteinase action on esters and amides.